Phosphate-Solubilizing Bacterium Acinetobacter pittii gp-1 Affects Rhizosphere Bacterial Community to Alleviate Soil Phosphorus Limitation for Growth of Soybean (Glycine max) - He, Donglan; Wan, Wenjie (Frontiers in Microbiology, 2021)
Phosphorus (P) availability is a major restriction to crop production, and phosphate-solubilizing bacteria (PSB) in soils are responsible for P turnover. However, it remains unknown whether the application of PSB can facilitate both inorganic and organic P transformation and enhance function of rhizosphere bacteria. In this study, we applied Illumina MiSeq sequencing, plate-colony counting, quantitative PCR, and multiple ecological analyses. We found the inoculation of PSB Acinetobacter pittii gp-1 significantly promoted the growth of soybean represented by better vegetation properties (e.g., plant height and root P), increased activities of phosphatase (4.20–9.72 μg/g/h) and phytase (0.69–1.53 μmol/g/d) as well as content of indole acetic acid (5.80–40.35μg/g/). Additionally, the application of strain A. pittii gp-1 significantly increased abundances of both inorganic and organic P-cycling-related genes (i.e., phoD, bpp, gcd, and pstS). More importantly, the application of A. pittii gp-1 could increase the function represented by P-cycling-related enzyme (e.g., phosphotransferase) of rhizosphere bacterial community based on functional profiling. To our knowledge, this is the first report that the application of PSB A. pittii promotes inorganic and organic P utilization, and increase the function of rhizosphere bacterial community. Therefore, the PSB A. pittii gp-1 could be a good candidate for the promotion of soybean growth.